Antioxidant and Antiradical Eﬀects of Extracts Derived From Cryopreserved Human Placenta - Narozhnyi, Stanislav V.; Rozanova, Kateryna D.; Bobrova, Olena M.; Nardid, Oleg A. (Problems of Cryobiology and Cryomedicine, 2019)
In this study the data concerning placenta low temperature storage impact on antioxidant action of its aque-ous-saline extracts towards erythrocytes under sodium nitrite-induced oxidative stress are provided. The research pro-tocol included two parts: the first one comprised a simultaneous exposure of erythrocytes to the extracts and nitrite, the second one referred to the nitrite addition to the erythrocytes, preliminary treated with the extracts. The level of oxidative stress was assessed by erythrocytes methemoglobin one, antiradical activity was evaluated by the extracts ability to reduce ABTS+ radical. Aqueous-saline extracts keep their protective ability toward erythrocytes under oxidative stress up to three and up to six months for the placenta stored –20°C and –80°C, correspondently. Placenta storage at –20°C for six months led to the lowering of protective effect, as well as antiradical activity down to 50% in comparison with fresh extracts. The 10–12 kDa fraction of the aqueous-saline extracts showed the highest protective effect, which did not change up to three and up to six months for the placenta, stored –20°C and –80°C, respectively. After six months for the placenta stored –20ºC the antiradical activity of this fraction was significantly reduced. Probl Cryobiol Cryomed 2018; 28(4): 322-332